2016
DOI: 10.1021/acs.jctc.6b00969
|View full text |Cite
|
Sign up to set email alerts
|

The Monomer Electron Density Force Field (MEDFF): A Physically Inspired Model for Noncovalent Interactions

Abstract: We propose a methodology to derive pairwise-additive non-covalent force fields from monomer electron densities without any empirical input. Energy expressions are based on the Symmetry-Adapted Perturbation Theory (SAPT) decomposition of interaction energies. This ensures a physically motivated force field featuring an electrostatic, exchange-repulsion, dispersion and induction contribution, which contain two types of parameters. First, each contribution depends on several fixed atomic parameters, resulting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 121 publications
0
115
0
Order By: Relevance
“…Note that the electrostatic term in the GAFF force field uses simple point charges and does not account for short-range screening due to the finite extent of the atomic electron densities, also known as the penetration effect 25 , 27 , 55 58 . While the inclusion of such screening makes the electrostatic term more physically sound, it is not recommended in our case.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the electrostatic term in the GAFF force field uses simple point charges and does not account for short-range screening due to the finite extent of the atomic electron densities, also known as the penetration effect 25 , 27 , 55 58 . While the inclusion of such screening makes the electrostatic term more physically sound, it is not recommended in our case.…”
Section: Methodsmentioning
confidence: 99%
“…The main drawbacks of these models are their increased complexity (more parameters) and increased computational cost. In addition, it was recently shown that polarization energy of atomic dipole polarizable force fields can deviate severely from the induction energy of Symmetry-Adapted Perturbation Theory (SAPT) calculations on the molecular dimers in the S66 set 25 . Because a polarizable force field and the SAPT induction term try to describe the same physics, this discrepancy discourages the use more expensive polarizable force fields.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] An extension has later been proposed by Vandenbrande et al to efficiently estimate the correction without any free parameter. 5 This is achieved by including the atomic-density population N i of atom i-the normalization term in Eq. (3).…”
Section: Charge Penetrationmentioning
confidence: 99%
“…5 The parameter q c corresponds to a core charge that is not subject to penetration effects, i.e., q = q c N, where q is determined from the multipole expansion.…”
Section: Charge Penetrationmentioning
confidence: 99%
See 1 more Smart Citation